2008
DOI: 10.1016/j.jasms.2007.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous iron(II) and iron(III) complexes with BINOLate ligands

Abstract: Electrospray ionization (ESI) of dilute solutions of 1,1=-bi-2-naphthol (BINOL) and iron(II) or iron(III) sulfate in methanol/water allows the generation of monocationic complexes of iron and deprotonated BINOL ligands with additional methanol molecules in the coordination sphere, and the types of complexes formed can be controlled by the valence of the iron precursors used in ESI. INOL (1,1=-bi-2-naphthol) is among the most important chiral ligands used in metal-mediated asymmetric synthesis [1]. Despite a hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The theoretical computations provided more detailed information for such a transient process, which showed that the N-atom on the neighboring pyrimidine might associate with the proton dissociation step from benzylamine, especially from the step A1 to A3. Totally, the step from A1 to B and propanol is an endoergic process with energy 9.7 kcal/mol (listed in Table [52] Such results also suggested the different gas-phase chemistries initiated by Fe(II) and Fe(III). The relative stabilities of the Fe(II) and Fe(III) complexes could also be explained by HSAB (hard and soft acids and bases).…”
Section: Gas-phase Smiles Rearrangement In the Tsq-ms And Fticr-msmentioning
confidence: 78%
See 1 more Smart Citation
“…The theoretical computations provided more detailed information for such a transient process, which showed that the N-atom on the neighboring pyrimidine might associate with the proton dissociation step from benzylamine, especially from the step A1 to A3. Totally, the step from A1 to B and propanol is an endoergic process with energy 9.7 kcal/mol (listed in Table [52] Such results also suggested the different gas-phase chemistries initiated by Fe(II) and Fe(III). The relative stabilities of the Fe(II) and Fe(III) complexes could also be explained by HSAB (hard and soft acids and bases).…”
Section: Gas-phase Smiles Rearrangement In the Tsq-ms And Fticr-msmentioning
confidence: 78%
“…Our ESI‐MS experimental results presented the gas‐phase reactivities of Fe(III) and Fe(II) complexes of pyrimidinyloxy‐ N ‐arylbenzylamines 1 – 6 in the solvent‐free condition, showing the distinct intrinsic catalytic effects of Fe(III) and Fe(II) cations: Fe(II) could initiate a train of fascinating gas‐phase reactions including skeletal rearrangement, retro‐ Michael reaction and some others while there is no evidence to show that Fe(III) complexes also occurred in such gas‐phase Smiles rearrangement reactions but give the interesting SET products 1 •+ – 6 •+ , as well as some fragment ions. Previously, Schröder and Schwarz studied the gaseous Fe(II) and Fe(III) complexes with BINOLate ligands, and the results showed that Fe(II) complexes and Fe(III) complexes have different gas‐phase chemistries: [(BINOLdiate)Fe] + , a Fe(III) species, undergoes decarbonylation as a typical fragmentation of ionized phenols and phenolates, while the [(BINOLate)Fe] + cation, a Fe(II) species, on the other hand, preferentially loses neutral FeOH to afford an organic C 20 H 12 O +• cation radical 52. Such results also suggested the different gas‐phase chemistries initiated by Fe(II) and Fe(III).…”
Section: Resultsmentioning
confidence: 99%
“…An accurate estimate of this amount of energy entails a fine control on all experimental variables and can only be accomplished with guided ion beam instruments purposely designed for energy‐resolved tandem mass spectrometry 45. However, experimentally simpler approaches can take advantage of the ability of the analytically oriented triple quadrupole tandem mass spectrometer to record fragment spectra at several defined values of center‐of‐mass collision energy and to examine them to obtain at least semi‐quantitative estimates of the involved energies 37–40, 46…”
Section: Resultsmentioning
confidence: 99%
“…45 However, experimentally simpler approaches can take advantage of the ability of the analytically oriented triple quadrupole tandem mass spectrometer to record fragment spectra at several defined values of center-of-mass collision energy and to examine them to obtain at least semi-quantitative estimates of the involved energies. [37][38][39][40]46 When this process is applied to the set of fragment spectra obtained from protonated disulfides such as glutathione disulfides and other analogues, the onset potential of the fragment appearance curves obtained for the same fragment (e.g., the 'sulfenium' fragment) from different precursor ions (such as from several glutathione heterodisulfides) appear very close to one another, as can be found in the left column of Fig. 2.…”
Section: Formation and Connectivity Of Disulfide Fragmentsmentioning
confidence: 99%
“…For alkan-2-ol ligands, RCHOHCH 3 , CID of the mass-selected [(BINOLate)Ni(RCHOHCH 3 )] þ ions leads to two primary channels, Reactions 1 and 2; at elevated collision energies, consecutive fragmentations of the BINOL residue are observed (e.g., decarbonylation) which are not pursued any further here [8] [12].…”
mentioning
confidence: 99%